2017
DOI: 10.1371/journal.pone.0179675
|View full text |Cite
|
Sign up to set email alerts
|

R-Modafinil exerts weak effects on spatial memory acquisition and dentate gyrus synaptic plasticity

Abstract: Modafinil is a wake promoting drug approved for clinical use and also has cognitive enhancing properties. Its enantiomer R-Modafinil (R-MO) is not well studied in regard to cognitive enhancing properties. Hence we studied its effect in a spatial memory paradigm and its possible effects on dentate gyrus long-term potentiation (DG-LTP). Clinically relevant doses of R-MO, vehicle dimethyl sulfoxide (DMSO) or saline were administered for three days during the hole-board test and in in vivo DG-LTP. Synaptic levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…The protein samples were separated by electrophoresis in 10% SDS-PAGE gel and transferred to PVDF membranes (GE Healthcare). The western blot procedure was performed as described previously ( Shanmugasundaram et al, 2017 ) with minor modifications. Briefly, the membrane was blocked for 1 h in 5% non-fat milk, 1x TBS, 0.05% Tween-20 and probed with the corresponding primary and secondary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…The protein samples were separated by electrophoresis in 10% SDS-PAGE gel and transferred to PVDF membranes (GE Healthcare). The western blot procedure was performed as described previously ( Shanmugasundaram et al, 2017 ) with minor modifications. Briefly, the membrane was blocked for 1 h in 5% non-fat milk, 1x TBS, 0.05% Tween-20 and probed with the corresponding primary and secondary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…R-modafinil, (R)-2-(benzhydrylsulfinyl)acetamide was also synthesized in house as reported previously [35] via a procedure based on the US 7,812,193 B2 patent application.…”
Section: Drugs and Treatmentsmentioning
confidence: 99%
“…In agreement with our study, Shanmugasundaram et al . showed that DMSO (same as our dosage) impairs spatial memory and decreases synaptic plasticity [ 27 ]. Also, Budinich et al .…”
Section: Discussionmentioning
confidence: 99%